Development and recovery of mechanical properties of self-healing cementitious composites with MgO expansive agent. (1st September 2017) - Sherir, Mohamed A.A.; Hossain, Khandaker M.A.; Lachemi, Mohamed
Highlights: Study self-healing capability of new cementitious composite with MgO expansive agent. Self-healing capability of samples is evaluated based on the recovery of strength and UPV. Variables used are specimen type, age, curing conditions and cracking/damage types. Air cured MgO composites show better self-healing capability compared to water cured ones. Abstract: This paper presents the performance of engineered cementitious composites (ECCs) produced with MgO utilized as expansive self-healing agent to heal micro cracks. ECCs capability to keep small crack width of less than 60 µm even under ultimate loads can stimulate the autogenous crack healing and thus, improving the mechanical properties of structural elements. Different test schemes were adopted to quantify the long-term self-healing capability of proposed ECC-MgO system (made of 5% MgO expansive agent 'MEA' as fly ash replacement in ECC matrix) through studying the development and recovery of strength (compressive and flexural) and Ultrasonic Pulse Velocity (UPV) of pre-loaded multiple damaged (cracked) cubic and prismatic specimens subjected to long term water and natural curing conditions. Test results indicated that preloaded cracked ECC-MgO specimens had high tendency to recover original mechanical properties of virgin (un-cracked) specimens through healing of micro-cracks. This study confirmed the self-healing capability of proposed ECC-MgO system.